A synchronous piezoelectric–triboelectric–electromagnetic hybrid generator for harvesting vibration energy. Issue 1 (17th November 2020) - Singh, Huidrom Hemojit; Kumar, Dheeraj; Khare, Neeraj
Abstract : The developed hybrid device and its various applications including powering of electrolysis, a digital calculator, and LEDs. Abstract : Combining different devices to harvest energy is a novel strategy to increase the efficiency and applicability of devices that harvest mechanical energy. In the present work, we designed and fabricated a hybrid generator by combining piezoelectric, triboelectric, and electromagnetic (EM) effects to harvest mechanical vibrations. With the selection of ZnO–PVDF, a highly piezoelectric material as one of the contacting materials for the triboelectric effect allowed us to combine both the piezoelectric and triboelectric effects without the need to fabricate each unit individually. Because of the design of the device, the electricity from each effect was generated simultaneously. We achieved a maximum open-circuit output voltage of ∼192 V and a short-circuit current of ∼2.78 mA from the piezoelectric–triboelectric and EM hybrid device. The hybrid system was shown to be able to charge a 10 μF capacitor up to a voltage of 7.35 V in a short period of 170 s, an achievement not possible with the individual units. The maximum saturation voltage measured across the capacitor increased after combining the trio of effects, i.e., the piezoelectric, triboelectric, and EM effects, a feature that expands the applicability of the device to power instruments requiring higher voltages. The application potentials of the hybrid device in powering a digital calculator, screw gauge meter, and electrolysis of water to generate H2 /O2 were demonstrated. The present work established a novel and practical approach to generate electricity from mechanical motions by combining piezoelectric–triboelectric and EM effects.